Understanding Demand When Reforming Water Supply and Sanitation : A Case Study from Sri Lanka - van den Berg, Caroline; Pattanayak, Subhrendu; Yang, Jui-Chen; Gunatilake, Herath (World Bank, Washington, DC, 2012)
Many countries are weighing urgent reforms to bring safe water supply and sanitation (WSS) services to hundreds of millions of poor city dwellers. Past reforms, unfortunately, have often ignored consumer preferences and perceptions, resulting in overly optimistic projections of the revenue potential of reform projects. When revenues fall short, private partners may seek to renegotiate their contract, resulting in tariff increases and other changes that increase project costs across the board. Such situations can undermine political commitment to reforms in general and to Private Sector Participation (PSP) in particular. Understanding consumers can help avoid such situations. Different groups of consumers have distinct preferences and perceptions that may influence their decisions about new water systems. Unfortunately, studies of consumers' water-related preferences are often deferred because collecting data takes time and costs money. Often there is pressure to complete reforms quickly sometimes to take advantage of a political opportunity so the necessary research is not done. In other cases, the challenge of increasing efficiency and improving governance may seem so daunting that the specific interventions required to make reform beneficial to the poor may be overlooked or consciously deferred.